2018
DOI: 10.1155/2018/8598054
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Extremely Low LDL-Cholesterol Levels and Its Prospects in Hyperlipidemia Management

Abstract: The risk of cardiovascular disease has been reported to have a linear relationship with LDL levels. Additionally, the currently recommended LDL target goal of 70 mg/dl does not diminish the CV risk entirely leaving behind some residual risk. Previous attempts to maximally lower the LDL levels with statin monotherapy have met dejection due to the increased side effects associated with the treatment. Nevertheless, with the new advancements in clinical medicine, it has now become possible to bring down the LDL le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Recent data confirm safety of very low levels of LDL-c down to 15 mg/dl. Combination therapy should be initiated after reaching the highest tolerable doses of statin [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Recent data confirm safety of very low levels of LDL-c down to 15 mg/dl. Combination therapy should be initiated after reaching the highest tolerable doses of statin [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Leptin particulates in cholesterol-regulating functions via proprotein convertase subtilisin/kexin type 9 pathway and down-regulates expression of LDL receptors in hepatocytes, leading to elevated plasma LDL-C levels and dyslipidemia [ 35 ]. High levels of HDL-C can lower your risk for cardiovascular diseases, while high LDL-C levels have opposite effects [ 36 , 37 ]. Among our postmenopausal participants, we observed the findings that circulating adiponectin levels are significantly positively associated with HDL-C levels ( Table 2 ) and leptin levels are highly correlated with LDL-C ( Table 3 ), consistent with previous reports [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…40 There were previous reports regarding the reduction LDL-c, TC and TG levels related decreased risk in cardiovascular complications. 41,42 A metaanalysis demonstrated that the reduction in LDL-C of lowrisk subjects with HMG-CoA reductase inhibitors and this LDL-C reduction associated cardiovascular mortality. 43 Our systematic review showed that triphala treatment significantly decreased FBS and HbA1c in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%